Nutrient dynamics under different regimes of stocking and cattle type of temperate pastures in Hokkaido, Japan. (15th July 2020) - Okui, Tatsuya; Yagi, Takanori; Yamada, Kazuki; Niwa, Yoshimasa; Asai, Kaho; Kumagai, Takashi; Yoshida, Yusuke; Hori, Kazuya; Ugaki, Ryosuke; Yamashita, Shigekazu; Kato, Yuta; Tsukasaki, Kentaro; et al.
Abstract: Fertilizer recommendations for day and night grazing of milking cattle on land in Hokkaido are based on previous studies of nutrient dynamics. This study confirmed the applicability of recommendations to different grazing conditions and conducted observations to extend the versatility of the fertilizer recommendation. We estimated the dynamics of fertilizer nutrients under various grazing regimes, namely with different cattle types (dairy heifers, beef breeding cows or beef heifers), stocking methods (rotational stocking or continuous stocking), seasons (throughout grass growing season or after harvest of the first crop) and times (24‐hr grazing or time restricted to 5– 9 hr/day). Body weight, herbage intake and excretion were measured, and the total intake and return of nutrients to the pasture were calculated. Nutrient removal by grazing, calculated as intake minus return through excretion, increased with herbage intake. Almost all the nutrients removed under grazing throughout the growing season approached the upper or lower limits of our previously reported levels. In many cases, changes in the amounts of soil nutrients with grazing were close to the estimated amounts removed from the soil in the grass growth periods. These results show that the pasture nutrient dynamics quantified in our previous study for lactating cattle are also applicable to dairy heifers and beef cattle and to time‐restricted grazing as well as grazing after 1st cut. Regression equations were obtained to predict the fertilizer recommendations from herbage intakes for these various grazing conditions.